Pattern and influencing factors of breastfeeding of working mothers in several areas in Jakarta - Rifan Fauzie; Rulina Suradi; Sri Rezeki S. Hadinegoro (Indonesian Pediatric Society Publishing House, 2007)
Background Breast milk contains many essential nutrition factors best for babies. The 1997 Indonesian Health Demography found that the proportion of exclusive breastfeeding was still low (52%) and increased to 55.1% in 2002. Due to increasing number of working mothers, promoting breast feeding among them should be performed properly. There are no data on exclusive breastfeeding rate and pattern among working mothers in Indonesia. Objective To describe exclusive breastfeeding rate and pattern among working mothers in several areas in Jakarta and the influ- encing factors. Methods A descriptive study using a questionnaire was conducted from October 2005 to February 2006. Subjects were working mothers who had 6 to 12 month old baby and breastfed and the baby had no congenital or chronic disease. Results Among 290 mothers interviewed, 40% worked at banks or insurance business, 34% were private employees, 25% medical staffs, and 2% were teachers. Almost 80% have exclusively breastfed for less than 4 months, 17% for 4 months, and only 4% for 6 months. Maternal leave, family support, mothers' knowl- edge, facilities at workplace, media influences, and working hours seemed to have no relations to breastfeeding rate. There were 122 (42%) mothers who had good knowledge about physiology of lactation, 155 of them (53%) had fair knowledge, and only 45% of them had poor knowledge. Conclusions The proportion of working mothers in several areas in Jakarta who have exclusively breastfed for 4 months is 17%, and only 4% of subjects do exclusive breastfeeding for 6 months. Most subjects have a good to fair knowledge about the physiology of lactation but it does not seem to influence the decision to exclu- sively breastfed their babies.